Internalisasi Nilai Moderasi Beragama dalam Pembelajaran PAI di Sekolah: Respons terhadap Etika Pergaulan Siswa - Aufa Fatchia Rahma; Maesaroh Maesaroh; Nur Azizatul Haqiah; Winda Islamitha Nurhamidah; Sibawaihi Sibawaihi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to describe how religious moderation values are internalized in Islamic Education (PAI) learning at SMAN 2 Sleman. Strengthening religious moderation is considered crucial to respond to the moral and social challenges experienced by Generation Alpha in today’s digital era. Core values such as tolerance, fairness, and balance need to be cultivated early to build students’ openness and appreciation for diversity. This research applied a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The results show that the internalization process occurs through teachers’ exemplary behavior, routine practices, and reflective-dialogue-based learning. The process is supported by an inclusive and cooperative school climate, while challenges arise from digital media influences and peer rivalry. Overall, religious moderation in PAI learning contributes significantly to shaping students’ moderate and respectful character in the school environment.